The legal uncertainty as an response of the right to the dilemmas of biotechnological advance, paradox or the only possible solution? - Montalvo Jääskeläinen, Federico de (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
In this complex future that is predicted for us, not only will we be able to be surpassed in our intellectual or physical capacities, incorporating an enormous technological apparatus into our environment and our own body, but we will be able to improve ourselves, and even before we are born, intervening directly on the embryo. The nature of the human is called into question, above all, when we alter it in its own essence, not only in its environment, and, furthermore, from its own beginning. It is, therefore, a substantial disruption and alteration ad intra of the human being, not ad extra, as occurs with technology, even though it also obviously has many effects within it. The changes that derive from Biotechnology and, specifically, from genomic editing, on the one hand, offer enormous potential to develop new concepts, methods and novel applications for the urgent challenges and needs of society. On the other hand, such biotechnologies are perceived as having the potential to challenge and, at times, blur the attitudes, values and cultural models of society itself. Obviously, the Law cannot be alien to such a challenge in view of the values, interests and rights in conflict. If the question that we must ask ourselves again is what is man or what is human nature, the Law must also offer answers that allow giving a contemporary legal meaning to such essence, questions that connect directly with the legal concept of dignity itself, not only as an ontological value of the human being, but also, taking into account the explicit terms of article 10.1 of our Constitution, as the foundation of political order and social peace.